The relationship between adverse childhood experiences (ACE), self-objectification, father-child bonding styles, and self-sexualizing behaviors - Lam, Rachel Jia Yi (Nanyang Technological University, 2022)
This study aimed to investigate the relationship between adverse childhood experiences (ACE), father-child bonding styles, self-objectification and self-sexualizing behaviors. In doing so, this study also intended to find out if the relationship between these variables were mediated by others approval-contingent self-worth (OASW). Thus, a sample of 269 participants, aged 21 to 35, were recruited via convenience sampling online using social media platforms Instagram, Telegram and Whatsapp. Participants were tasked to complete a survey including demographics, ACE questionnaire, Parental Bonding Instrument, OASW questionnaire, self-objectification questionnaire, self-sexualizing behaviors questions and a shortened form of the social desirability scale. Results found that ACE was significantly associated with self-objectification (F = 14.819, p = 0.000). Additionally, paternal care (F = 11.501, p = 0.000) and paternal overprotection (F = 10.148, p = 0.000) were also significantly associated with self-objectification. None of the other hypothesized relationships were observed. Additionally, the relationship between ACE and self-objectification was the only one significantly mediated by OASW. In conclusion, ACE and paternal overprotection were significantly and positively associated with self-objectification, while paternal care was significantly and negatively associated to self-objectification. This paper suggested areas for future research and discussed applying its findings to reducing self-objectification.